2013
DOI: 10.1007/s10856-013-5029-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes reinforced chitosan films: mechanical properties and cell response of a novel biomaterial for cardiovascular tissue engineering

Abstract: Carbon nanotubes have been proposed as fillers to reinforce polymeric biomaterials for the strengthening of their structural integrity to achieve better biomechanical properties. In this study, a new polymeric composite material was introduced by incorporating various low concentrations of multiwalled carbon nanotubes (MWCNTs) into chitosan (CS), aiming at achieving a novel composite biomaterial with superior mechanical and biological properties compared to neat CS, in order to be used in cardiovascular tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…To determine the chemical stability, Cs biocomposites were dipped into an acidic medium (sulfuric acid [H 2 SO 4 ] and formic acid [HCOOH]), basic (potassium hydroxide [KOH) and hydroxylamine [NH 2 OH]), polar solvents (water [H 2 O), and methanol [CH 3 OH]), nonpolar solvents (n‐Hexane [C 6 H 14 ) and chloroform [CHCl 3 ]) and aprotic solvent (dimethyl sulfoxide [DMSO, C 2 H 6 OS) and THF [C 4 H 8 O]). Normally, the chemical stability of Cs biocomposites is distinguished by its solubility and changes in the solvent color from colorless to yellow‐brownness . However, in this study, the stability of Cs/nanocellulose biocomposites film was monitored by measuring the mass loss of Cs/nanocellulose biocomposites after dipping and stirring processes for 24 h in a specific solvent medium at 28°C (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To determine the chemical stability, Cs biocomposites were dipped into an acidic medium (sulfuric acid [H 2 SO 4 ] and formic acid [HCOOH]), basic (potassium hydroxide [KOH) and hydroxylamine [NH 2 OH]), polar solvents (water [H 2 O), and methanol [CH 3 OH]), nonpolar solvents (n‐Hexane [C 6 H 14 ) and chloroform [CHCl 3 ]) and aprotic solvent (dimethyl sulfoxide [DMSO, C 2 H 6 OS) and THF [C 4 H 8 O]). Normally, the chemical stability of Cs biocomposites is distinguished by its solubility and changes in the solvent color from colorless to yellow‐brownness . However, in this study, the stability of Cs/nanocellulose biocomposites film was monitored by measuring the mass loss of Cs/nanocellulose biocomposites after dipping and stirring processes for 24 h in a specific solvent medium at 28°C (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Several efforts have been done to improve its chemical stability by reinforcing Cs. Kroustalli et al used multiwalled carbon nanotubes (MWCNTs) on Cs biocomposites to improve its structural stability and properties. They reported that Cs biocomposites strengthened its structural stabilty with the addition of MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…That is, carbon nanotubes are seriously considered as the active elements for logic circuits, possibly replacing silicon [39][40][41]. There is also an enormous effort focused on using nanotubes to strengthen composite materials [42][43][44]. Currently there is widespread interest in employing graphene in supercapacitors due to its high surface area [32,45].…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in the tensile strength and modulus were ascribed to the uniform dispersion of MWCNTs covalently linked to the CS matrix. Kroustalli et al evaluated the mechanical properties and cell response of CNTs reinforced chitosan films. In their research, a new polymeric composite material was prepared by incorporating various low concentrations of MWCNTs into CS, with the purpose of achieving a novel composite biomaterial with far superior mechanical and biological properties compared with pure CS, in order to be used in cardiovascular tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%